Analysis of Usability and User Experience on News Portals Across Generation from Baby Boomers to Generation Alpha - Dewanti, Lintang Nataniela; Sari Dewi, Ratna (SURYA TEKNIKA, 2026)
The rapid development of digital technology in Indonesia has not been fully supported by adequate digital literacy, creating generational gaps in technology use. These differences may influence usability and user experience (UX) when users access online news websites. This study aims to analyze differences in usability and UX among generations on the Detik.com news website using a quantitative approach. A total of 400 respondents participated in this study, consisting of Baby Boomers (17), Generation X (99), Millennials (124), Generation Z (128), and Generation Alpha (32). The Kruskal-Wallis test was applied to examine significant differences in usability and UX among generational groups, while the Mann-Whitney test was used as a post hoc analysis to identify specific differences between generation pairs. The results show significant differences among generations, with Generation Z demonstrating the highest user experience, while Generation Alpha obtained the lowest results, particularly in the learnability aspect. The most dominant differences were found in comparisons involving Generation Alpha, whereas Generation X and Millennials showed no significant differences. These findings contribute to understanding intergenerational differences in usability and UX on digital news platforms and provide practical implications for developing adaptive, accessible, and user-centered website designs.